Stepping (Designing) the process of pupils’ writing chemical reactions’ equations for other pupils - Jyż-Kuroś, Danuta; Zimak-Piekarczyk, Paulina; Kopek-Putała, Wioleta; Nodzyńska-Moroń, Małgorzata (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
The main goal of the project was to make students of the 1st grade of high school aware of the complexity of the process of writing and balancing chemical equations. The use of various teaching methods (project method, brainstorming, snowball, Ishikawa diagram) was aimed at creating in students the intrinsic motivation that is needed to support their own learning process. It is hypothesized that students are unaware of the complexities of writing and balancing chemical equations. Lack of this awareness causes students to struggle with this issue, which results in their discouragement. As a result of the project, students prepared instructions that gradually described what steps should be taken to write and balance a given chemical reaction equation. As a result of working on the project, students realized what are the next steps in writing and balancing chemical equations. The attitude of students has changed - fewer students think that this issue is difficult.